Numerical Simulation of Fire Spread and Evacuation for Teaching Building - SUN Chao; LIU Yue-chan; WANG Bo; JIANG Yong-qing (Journal of Harbin University of Science and Technology)
University teaching building is the focus of the fire safety management with staff density fire load In order to study the fire safety characteristics of this kind of buildings, the fire dynamic simulation software Pyrosim and the personnel evacuation simulation software Pathfinder were used to study the law of fire spread and development and the emergency evacuation The model was established to simulate and analyze the fire and evacuation of typical teaching building by full size numerical simulation According to the simulation results and data, the paper analyzes the fire spread, smoke diffusion, toxic gas concentration, temperature distribution and visibility change in different time of the fire in the teaching building, and the emergency evacuation situation The results show that the model can effectively carry out the fire analysis of teaching building, which can provide the reference basis for the fire safety design of similar buildings, and has a certain guiding role in the fire emergency planning and on  site fire prevention